An expert opinion process to prioritize One Health information needs during a zoonotic disease outbreak - Rachel Nalepa; Jennifer Provencher; Jolene A. Giacinti; Alana Wilcox; Christopher M. Sharp; Robert A. Ronconi; James O. Leafloor; Steven Duffy; Michael Brown; Stephanie Avery-Gomm (Canadian Science Publishing, 2024)
There is a global movement to implement a One Health approach across sectors to holistically address emerging issues that have implications for public, animal, and environmental health. The operationalization of a One Health model can support knowledge sharing and build an evidence base for designing research programs and decision-making tools to evaluate and mitigate intersectoral health challenges. In late 2021, the highly pathogenic avian influenza virus (HPAIV) H5N1 2.3.4.4b was detected in eastern Canada, and subsequently spread throughout the flyways of North America. Given the multiyear persistence of the current HPAIV in Europe and the continued detections in North America, Environment and Climate Change Canada and partners recognized the need to prioritize HPAIV-related information needs to inform future decision-making and management. In early 2023, we carried out an expert opinion exercise with partners from across One Health domains and expertise to prioritize information needs related to the conservation and management of migratory birds in Canada. The results informed on-the-ground programming for migratory bird activities in 2023 and onwards. The process illustrates how a One Health lens can be applied with a conservation focal point, using dedicated facilitation to synthesize expert opinions across groups with non-overlapping mandates.